Finite Element Analysis of Aluminum Based R22 Car Wheel Design Modification - Salman Alfarisi; Riyan Ariyansah; Dan Mugisidi (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2024)
The wheels are one of the main parts of the vehicle. To make car wheels, manufacturers must complete several stages. Especially in the design of the wheels. This study aims to determine the comparative value of three different types of wheels with the same material using aluminum type 6061-T6 (SS). We will test the three-wheel models, namely model 1, model 2, and model 3, with a force of 3000 N and a pressure of 800 N to compare their performance. This test uses Solidworks 2019 software with the finite electronic analysis (FEA) method. The results obtained are the value of Von Misses stress, resulting displacement, equivalent strain and its deformation, and factor of safety. The dimensions of the wheels are 22 inches. The results of the best Model 3 alloy wheel research indicate that the design process is easier. These wheels have a Von Misses stress value of 11.02 MPa with a resulting displacement value of 0.021 mm, an equivalent strain of 0.000096, a safety factor of 25, and a deformation value of 1. Based on these results, model 3 alloy wheels are safe.